BEES-HAUS preventing urethral stricture recurrence by restoring the integrity of urothelium and its further simplified version, the BHES-HAUS - Horiguchi, Akio; Vaddi, Surya Prakash; Rajappa, Senthilkumar; Preethy, Senthilkumar; Abraham, Samuel J. K. (Frontiers in Bioengineering and Biotechnology, 2025)
Graphical AbstractDiagram illustrating interventional treatment approaches for urethral stricture, emphasizing urothelial integrity in preventing stricture recurrence. It compares procedures such as balloon dilatation and urethrotomy which leave the sub-urothelium exposed to urine leading to inflammation to that of procedures such as BEES-HAUS in which transplanted buccal mucosal cells and in BHES-HAUS transplanted buccal tissue bits, both mixed with Festigel, engraft and restore the urothelial integrity. BEES-HAUS involves a two-week in vitro culture, while BHES-HAUS processes tissue in the operating room in single sitting. Both methods aim for effective urethral treatment using autologous buccal mucosal epithelium.Diagram illustrating interventional treatment approaches for urethral stricture, emphasizing urothelial integrity in preventing stricture recurrence. It compares procedures such as balloon dilatation and urethrotomy which leave the sub-urothelium exposed to urine leading to inflammation to that of procedures such as BEES-HAUS in which transplanted buccal mucosal cells and in BHES-HAUS transplanted buccal tissue bits, both mixed with Festigel, engraft and restore the urothelial integrity. BEES-HAUS involves a two-week in vitro culture, while BHES-HAUS processes tissue in the operating room in single sitting. Both methods aim for effective urethral treatment using autologous buccal mucosal epithelium.